(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
This paper is an elaborated version of my presentation at the round-table about ’Trauma, Uncertainty and Crisis’ at the First World Congress of Existential Therapy in London in May 2015. Its main purpose is to introduce a distinction between two different types of trauma which is overlooked even by authors who rely on existential philosophy for their concept of trauma. I had the idea that there must be more than just one type of trauma because I came to understand my neurotic patients as traumatized too, albeit not in the usual sense. Therefore I plead for differentiating between two types of trauma. I term the usual type of trauma ’ontic’, respectively ’existentiell’, the other type ’ontological’, respectively ’existential’.1